Non-Pharmaceutical Strategies for Subjective Cognitive Decline in Aging - Yongmei, Hou (Pharmaceutical Science: New Insights and Developments Vol. 4, 2025)
Background: Subjective cognitive decline (SCD) is a preclinical stage and risk factor of Alzheimer’s disease. Early detection and effective intervention of SCD are of great significance in preventing AD. Nowadays, non-pharmaceutical interventions are increasingly being recognized and valued. Objective: To introduce the reason, principle, and major method of Non-pharmaceutical Intervention for SCD, with a focus on reviewing their application and efficacy. Methods: Taking “non-pharmaceutical intervention” and “subjective cognitive decline” or “phycological intervention” and “subjective cognitive decline” or “behavioral intervention” and “subjective cognitive decline” as keywords, a literature retrieval is conducted to search for academic full-text literature published in Chinese or English in the past 15 years. The literature sources included journals, dissertations, and conference papers from databases such as PubMed, Web of Science, CINAHL Plus, Scopus, Embase, PsycINFO, and CNKI. Results: Forty-seven articles were included. Previous literature has shown that there are a variety of non-pharmaceutical intervention methods for SCD. Non-pharmaceutical intervention can reduce the elderly SCD patients' stress levels and negative emotions, raise their cognitive function (especially attention and memory), and related physiological and biochemical indicators, enhance their social participation and improve their quality of life. Conclusion: The efficacy of non-pharmaceutical intervention for SCD is increasingly recognized. However, there is a limitation in research regarding their effectiveness in managing SCD. Additionally, their operating procedures need to be standardized, and further verification of their efficacy is required.